Clinic Management System - Saputra, Gilas Adi; Budiarto, Sabar; Pramadhan, Rivaldiansyah; Rivai, Adriean Baihaqi; Athalla, Raffi Zaidan (Journal Collabits, 2024)
A Clinic Management System (CMS) is a web-based application designed to streamline the management of clinic operations, including patient registration, appointment scheduling, medical records, and billing. The system utilizes PHP for server-side scripting, allowing for dynamic content creation and seamless interaction with the database. MySQL is used as a relational database management system (RDBMS) to securely store and manage patient, appointment, and medical record data. Visual Studio Code (VS Code) serves as the primary integrated development environment (IDE) for building and debugging applications, offering features such as syntax highlighting and version control integration. This CMS aims to increase efficiency, reduce administrative errors, and improve the overall experience for patients and healthcare providers.